2013
DOI: 10.1188/13.onf.454-463
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision Making Among Individuals With Cancer in Non-Western Cultures: A Literature Review

Abstract: Shared decision making may be new to patients from non-Western cultures, necessitating assessment, education, and support. Non-Western patients may value having family and friends accompany them when a cancer diagnosis is given, but assumptions based on culture alone should not be made. Nurses should determine patient preferences for diagnosis disclosure, information, and participation in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 51 publications
(84 reference statements)
1
55
0
Order By: Relevance
“…Non-Western physicians are also reluctant to inform their patients of their cancer diagnosis and prefer to disclose the diagnosis to the family. [13] A study reported that Japanese patients were not given the opportunity to participate in decision making and forced to make treatment decisions without being given sufficient information. [13]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-Western physicians are also reluctant to inform their patients of their cancer diagnosis and prefer to disclose the diagnosis to the family. [13] A study reported that Japanese patients were not given the opportunity to participate in decision making and forced to make treatment decisions without being given sufficient information. [13]…”
Section: Introductionmentioning
confidence: 99%
“…[13] A study reported that Japanese patients were not given the opportunity to participate in decision making and forced to make treatment decisions without being given sufficient information. [13]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in many cultures disclosure of diagnostic and prognostic information to the patient is discouraged in an effort to protect the patient from distress [5,6]. Cultural values and communication expectations common in non-western cultures [7,8] may prevail even when patients and families migrate to countries with different communication norms.…”
Section: Introductionmentioning
confidence: 99%
“…Patients from Eastern cultures may value being accompanied by family and friends when cancer is diagnosed; however, assumptions based on culture should be avoided. Nurses should determine patient preferences for diagnosis disclosure, information requirements, and participation in decision making (Obeidat, Homish, & Lally, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%